Playing "CABE" (Searching and Whispering) to Increase Children’s English Vocabulary - Ndraha, Venny Eria; Kurniawan, Mozes (Jurnal Pendidikan Usia Dini, 2019)
This study aims to increase children English vocabulary aged 5-6 years old by playing CABE or searching and whispering. This research is classroom action research that was conducted in Marsudirini Sang Timur Kindergarten, Salatiga. The Subjects of the study were 20 B1 kin-dergarten children. Data was collected by teaching English vocabulary by playing CABE in some cycles which includes four stages in the form of cycles, there are (1) planning; (2) im-plementation; (3) observation; and (4) reflection. Research instruments used in this research was in sheets observation checklist. The results of a percentage of pre-cycle was 13 %, cycle I was 31 % in first meeting and was 66 % in the second meeting, cycle II was 75 % per-formed in only one meeting. There is an improvement in pre-action and any action on each meeting until it reaches 75 %. Keywords: Early childhood, English vocabulary, “CABE” method, Learning English References Bawono, Y. (2017). Kemampuan berbahasa pada anak prasekolah : Sebuah kajian pustaka. Prosiding Temu Ilmiah X Ikatan Psikologi Perkembangan Indonesia. Chamot, A. U. (1987). Toward a Functional ESL Curriculum in the Elementary School, in Long, Michael H. & Richards, Jack C. (eds.) Methodology in TESOL. New York: Newburry House Publishers. Fromkin, V., Rodman, R., & H., & N. (1990). An Intoduction to Language. New York, NY: Avon Books.İlin, G., Kutlu, Ö., & Kutluay, A. (2013). An Action Research: Using Videos for Teaching Grammar in an ESP Class. Procedia - Social and Behavioral Sciences. https://doi.org/https://doi.org/10.1016/j.sbspro.2013.01.065 Imam, I. (2016). Meningkatkan Kemampuan Menyimak Siswa Kelas I Melalui Teknik Permainan Pesan Berantai Pada Pembalajaran Bahasa Indonesia. PEDAGOGIA: Jurnal Pendidikan. https://doi.org/https://doi.org/10.21070/pedagogia.v3i2.62 Khairani, A. I. (2016). Pendidikan Bahasa Inggris Untuk Anak Usia Dini. Digilib.Unimed.Ac.Id. Kurniawan, M., & Tanone, R. (2016). Mobile learning in TESOL: A golden bridge for enhancement of grammar awareness and vocabulary mastery? Asian EFL Journal. Matondang, E. M. (2005). Menumbuhkan Minat Belajar Bahasa Inggris Anak Usia Dini melalui Lagu dan Gerak. Jakarta: Jurnal Pendidikan Penabur. Montessori, M. (1991). The discovery of the Child. New York: Ballatine Book. Muflihah, M. (2019). Pentingnya Peran BAhasa dalam Pendidikan Usia DIni (PAUD). ThufuLA: Jurnal Inovasi Pendidikan Guru Raudhatul Athfal. https://doi.org/https://doi.org/10.21043/thufula.v2i2.4642 Mustafa, B. (2007). Pendidikan Anak Usia Dini. Musthafa, B. (2010). Teaching English to Young Learners in Indonesia : Essential Requirements. Educationist. Nugrahani, D., Egar, N., Sumardiyani, L., & Wardoyo, S. L. (2017). PENDIDIKAN ANAK USIA DINI BERBASIS LIFE SKILLS. E-DIMAS. https://doi.org/https://doi.org/10.26877/e-dimas.v2i1.102 Nurjanah, N, Dwiastuty, Nina, Susilawati, S. (2015). Mengenalkan Model Pengajaran Edutainment Mengajarkan Bahasa Inggris Pada Anak–Anak Usia Dini. Faktor. Jurnal Ilmiah Kependidikan. Nurmadiah, N. (2018). Strategi Pembelajaran Anak Usia Dini. Al-Afkar : Jurnal Keislaman & Peradaban. https://doi.org/https://doi.org/10.28944/afkar.v3i1.101 Nurvitasari, M. D. (2016). Penerapan Aspek Perkembangan Anak Usia Dini Dalam Media Macca (Balok Susun Interaktif). O’Grady, W. (2008). Innateness, universal grammar, and emergentism. Lingua. https://doi.org/https://doi.org/10.1016/j.lingua.2007.03.005 Santrock, J. (n.d.). Adolesence (Fifth Edit). New York, NY: McGrawHill Company Inc. Sophya, I. V. (2019). Desain Pembelajaran BAhasa Inggris untuk Pendidikan Anak Usia Dini. ThufuLA: Jurnal Inovasi Pendidikan Guru Raudhatul Athfal. https://doi.org/https://doi.org/10.21043/thufula.v2i2.4639 Tomlinson, B. (2012). Materials development for language learning and languange teaching. https://doi.org/https://doi.org/10.1017/S0261444811000528 Vygotsky, L. S. (1986). Thought and Language. Cambridge, M.A.: The MIT Press. Wiratno, T., & Santosa, R. (2003). Bahasa, Fungsi Bahasa, dan Konteks Sosial. Bahasa, Fungsi Bahasa, Dan Konteks Sosial. Yamin, M. (2010). Panduan Pendidikan Anak Usia Dini. Jakarta: Gaung Persada Pers. Zaini, A. (2015). Bermain sebagai metode pembelajaran bagi anak usia dini. ThufuLA: Jurnal Inovasi Pendidikan Guru Raudhatul Athfal.